Educational Financing Management For The Enhancement Of Education Quality - Sonny Muhammad Ikhsan Mangkuwinata; Sri Wardhani; Rosyidha Tanjung; Wardah; Saipin Ali Muhtaram (STMIK Indonesia Banda Aceh, 2026)
The quality of a nation’s education system is strongly influenced by the management of resources, particularly financial resources, which are one of the national education standards. This study employs a literature review approach by analyzing books, journal articles, and scholarly works related to educational financing. The results indicate that sufficient and properly managed funding has a positive impact on school quality, learning processes, and student outcomes. Sound financial management is based on the principles of accountability, transparency, integrity, consistency, efficiency, and effectiveness, carried out through budgeting, allocation, implementation, monitoring, and evaluation. Previous studies highlight that inadequate financing leads to substandard results, while effective financing enhances teacher professionalism, infrastructure provision, and institutional credibility. In addition, the implementation of total quality management (TQM) emphasizes continuous improvement, leadership focus, stakeholder collaboration, and intrinsic motivation as key strategies for quality enhancement. In conclusion, educational financing management plays a decisive role in improving the quality of education, and its effectiveness depends on professional administration, active stakeholder involvement, and compliance with national education standards.